DISCOVERY LEARNING PADA PEMBELAJARAN BAHASA INDONESIA SEKOLAH DASAR: SYSTEMATIC LITERATURE RIVIEW - Fitri, Trinindi Eriswan; Syahrul Ramadhan; Elfia Sukma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning Indonesian in elementary schools requires the use of appropriate learning models. One of the learning models that is recommended to be implemented in the 2013 curriculum and the independent curriculum is the discovery learning model. This research aims to determine research trends, research focus and research that is still rarely researched as well as analyzing the results of previous research related to the discovery learning model in Indonesian language learning in elementary schools.. The research method used is a Systematic Literature Review (SLR). The results of the research show that the trend of research carried out is Classroom Action Research with the research focus being integrated thematic and student learning outcomes and research that is still rarely carried out is quantitative research